PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA KELAS IX SMP NEGERI 1 FANAYAMA - Antonius Sarumaha (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
This research was carried out to respond to students' low mathematical problem-solving ability which has an impact on academic achievement. The main factor identified was teaching practices that were less attractive so as not to encourage active student participation. The purpose of this study was to assess the effectiveness of the Realistic Mathematics Approach in improving students' ability to solve mathematical problems. The design used was in the form of a quasi-experiment with a quantitative approach, involving 38 grade IX students of SMPN 1 Fanayama as a sample. The research instrument is in the form of a test that has been validated and tested, consisting of 10 questions with 7 pretest questions and 7 posttest questions. The results of the hypothesis test showed a significant improvement through this approach, with a significance value (t calculated) < 0.05. Based on these findings, it is recommended that teachers adopt the Realistic Mathematics Approach as an alternative learning strategy to optimize students' problem-solving abilities. Keywords: Realistic Math Approach, Math Problem-Solving Ability, Students